Formação e manutenção de classes de equivalência: efeitos da magnitude das consequências e do uso de um procedimento gamificado - Santos, Alceu Regaço dos (Universidade Federal de São Carlos, 2021)
Studies have showed that the relations between equivalence class stimuli can vary in function of numerous experimental parameters. However, few studies investigated the effect of consequences as an independent variable. This study is divided in three experiments, which have as general purpose to evaluate the effect of using reinforcing and punishing consequences in the formation and maintenance of equivalence relations. The Experiment 1 and 2 compared the use of contingencies of reinforcement and punishment exclusively or together, for training two potential classes of stimuli with four member each. It was used a traditional Matching-to-Sample procedure and the participants were distributed in three groups related with the consequences used: Reinforcement Group (R), Reinforcement-Punishment Group (R-P) and Punishment Group (G). A bigger number of participants in Group R reached the criteria for the formation of the equivalence classes when compared with the other groups. Experiment 3 had as specific objective an evaluation of the effect of the magnitude of the reinforcement and punishment consequences in the formation and maintenance of equivalence classes. For data collection, a gamified version of the MTS (the game Miner Troubles, developed for the study) was used, adapted for online data collection, due to limitations resulting from the Covid-19 pandemic. 56 people (between 18 and 57 years old) participated in the research, randomly distributed among three groups: the More-Earning Group (M-E), the Balanced Group (B) and the More-Loss Group (M-L). In the first group, the participants gained 4 points when they choose correctly and lost 1 point when making a mistake; in the second group, the participants gained 1 point when they choose correctly and lost 1 point when making a mistake; and in the third group, the participants gained 1 point when they choose correctly and lost 4 points when they choose incorrectly. As the results, the use of a greater magnitude of punishment interfered in the learning of conditional relationships and in the emergence of untrained relationships: the performance of M-L participants was less accurate in the Symmetry and Relationship Maintenance Tests compared to other groups. This experiment extends the findings of other studies on the effect of punishment on discriminative learning and gives rise to a discussion about the use of punishment more intensely in learning.
Formation and maintenance of equivalence classes: the effects of magnitude of consequences and the use of a gamified procedure
Keywords: Magnitude das consequências; Classes de equivalência; Manutenção de classes; Gamificação; Matching-to-sample; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO